Development of Authentic Assessment with Project Based Learning Approach in Primary School Students - Cahyono, Budi Tri; Prihatin, Relly; Suparmi, Suparmi; Sukmawati, Fatma; Santosa, Eka Budhi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research is a research on the development of authentic assessment instruments. The types of data used in this study are quantitative and qualitative data. Quantitative data comes from scores of assessment experts, learning experts, and practitioners. Qualitative data includes comments and suggestions for product improvements from assessment experts, learning experts, and practitioners. The products produced in this research and development are in the form of Project Task Books and Authentic Assessment Instruments on Project-Based Learning Theme 8. The Project Project, Project Book product, refers to the Authentic Assessment Instrument on Project-Based Learning. The Project Task Book is used in Theme 8 Subtheme 3. Students must complete two project assignments. The results of the product feasibility test show that the Project Task Book is very feasible to implement. First, feasibility is assessed from content validity of 87%, construct validity of 87%, and practicality of 78%. The Authentic Assessment Instrument product on Project-Based Learning Theme 8 refers to three feasibility aspects. First, the feasibility of the guideline target is 83%. Second, the feasibility of the content of the guidelines is 88%. Third, the feasibility of the code of practice is 75%. This product can be an alternative for teachers to assess students' abilities in project assignments. Teachers can use this assessment instrument product more creatively and innovatively, for example, by designing project assignments according to the region. This product can be disseminated in teacher competence, educational journals, and social media.